Analysing Pakistan’s fisheries legislation and institutional framework: integrating Sustainable Development Goal 14 within the scope of International Fisheries Law - Lina, Liu; Murad Zaib Butt, Muhammad (Frontiers in Marine Science, 2025)
International Fisheries Law (IFL) provides innovative approaches to fisheries governance at national levels. The emergence of Sustainable Development Goal 14 (SDG 14) is phenomenal for fisheries because it creates new means for implementing IFL. Under SDG 14, fisheries governance for sustainable fisheries has become a complex and challenging task for any state. Developing States like Pakistan are struggling to achieve SDG 14 with new approaches to fisheries governance. The current situation of fisheries governance in Pakistan motivated the content of this research paper. This research paper adopted the comprehensive literature review (CLR) methodology to analyse existing fisheries governance mechanisms in Pakistan. Besides CLR, the paper also analysed a ‘case study’ on fisheries governance of Pakistan entitled ‘National Policy and Strategy for Marine Fisheries. Furthermore, one hundred sixty-seven research articles and national and international legislation on fisheries governance from 2010 - 2023 are analysed. The results of the CLR methodology suggested that an extensive integrated mechanism under a comprehensive framework should be developed for fisheries governance. The framework forwarded a policy mechanism incorporating sustainable development goals with SDG 14 that should be implemented coherently for sustainable fisheries. The discussion followed the analysis and suggested that regional to local and bottom-up and top-down approaches in fisheries governance are required to address the challenges to sustainable fisheries in Pakistan. The conclusion of the discussion portrayed that future research related to fisheries governance in Pakistan shall be based on the practical implementation of SDG 14.